Disrupted Families and Dislocated Fatherhood: Economic Challenges Driving Father Absence in South Africa - Fazel Ebrihiam Freeks (Ovidius University Annals: Economic Sciences Series)
Numerous voices of disrupted families are expressing themselves more loudly, and visible consequences are observed in countless broken families. Destructive social issues, such as toxic fatherhood, father absence, and disengaged or unavailable fathers, have resulted in significant challenges within families. Contributing factors include the breakdown of family structures, HIV/AIDS, the COVID-19 pandemic, rising divorce rates, and the increasing complexity of family dynamics. The absence of fathers, often linked to the disintegration of nuclear families, has become a significant concern, particularly in the South African context. Over the past four decades, researchers have made substantial progress, developing and refining conceptual frameworks to clarify human fatherhood.